2021
DOI: 10.1177/15459683211032977
|View full text |Cite
|
Sign up to set email alerts
|

Recovery of Visuospatial Neglect Subtypes and Relationship to Functional Outcome Six Months After Stroke

Abstract: Background/Objective. This study aims to investigate how complex visuospatial neglect behavioural phenotypes predict long-term outcomes, both in terms of neglect recovery and broader functional outcomes after 6 months post-stroke. Methods. This study presents a secondary cohort study of acute and 6-month follow-up data from 400 stroke survivors who completed the Oxford Cognitive Screen’s Cancellation Task. At follow-up, patients also completed the Stroke Impact Scale questionnaire. These data were analysed to … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
33
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 36 publications
(35 citation statements)
references
References 72 publications
2
33
0
Order By: Relevance
“…Within the consecutive sample included in this investigation 28.5% exhibited right-lateralised and 15.7% exhibited left-lateralised neglect. This finding is in line with previous research demonstrating that neglect deficits regularly occur following both right and left hemisphere damage ( Moore et al, 2021 ; Stone et al, 1992 ; Ten Brink et al, 2017 ). Similarly, as in previous studies, egocentric and allocentric neglect were found to be behaviourally doubly dissociated ( Chechlacz et al, 2010 , 2012 ).…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…Within the consecutive sample included in this investigation 28.5% exhibited right-lateralised and 15.7% exhibited left-lateralised neglect. This finding is in line with previous research demonstrating that neglect deficits regularly occur following both right and left hemisphere damage ( Moore et al, 2021 ; Stone et al, 1992 ; Ten Brink et al, 2017 ). Similarly, as in previous studies, egocentric and allocentric neglect were found to be behaviourally doubly dissociated ( Chechlacz et al, 2010 , 2012 ).…”
Section: Discussionsupporting
confidence: 92%
“…Conversely, right egocentric neglect was found to be most strongly associated with damage to left hemisphere occipital areas while right allocentric neglect was related to damage to voxels within the left internal capsule white matter. While there was some degree of overlap (6.45%) between the neural correlates associated with left egocentric and left allocentric neglect, the voxels associated with right This finding is in line with previous research demonstrating that neglect deficits regularly occur following both right and left hemisphere damage (Moore et al, 2021;Stone et al, 1992;Ten Brink et al, 2017). Similarly, as in previous studies, egocentric and allocentric neglect were found to be behaviourally doubly dissociated (Chechlacz et al, 2010(Chechlacz et al, , 2012.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…People with more severe allocentric neglect are less likely to make a full recovery from visuospatial neglect, potentially contributing to ongoing difficulties with walking safety. 56 For these reasons it would be advisable to continue to explore visuospatial neglect as a predictor for walking recovery, taking neglect subtypes into consideration.…”
Section: Discussionmentioning
confidence: 99%